Framework for infrastructure risk analysis to pedestrians in a university campus parking - Bezerra, Barbara Stolte [UNESP]; Manzato, Gustavo Garcia [UNESP]; Mello, Silas Volpon de [UNESP]; Peixoto, Anna Silvia P. [UNESP]; Batistão, Mariana Dias Chaves [UNESP] (My University, 2019)
This paper presents a framework to analyze the pedestrian’s risks due to infrastructure problems in a university campus parking. A geographic information system (GIS) database was created containing data about: cartographic, parking spots, problems of infrastructure and field observations notes. In addition, an analysis of parking capacity and demand was performed, resulting in an Average Occupancy Rate (AOR) of the campus parking. A checklist for field observations was created for the pedestrian’s risk analysis, where critical locations could be observed in a thematic map by applying spatial analysis tools. This framework created the first campus database, which has already supported the implementation of some actions for reducing risks to pedestrians. This fact highlights the importance of the framework for the future planning and management of the campus’s traffic and parking systems, which can be replicated to similar cases involving risk analysis at university campus parking, due its straightforwardness and low cost for implementation.
Keywords: Parking lot; Pedestrians; Risk analysis; Road infrastructure; University campus